Design of an Automatic Water Pump on a Traditional Boat - Ihsan, Ihsan; Ilham, Dirja Nur; Candra, Rudi Arif; Yunan, Amsar; Hardisal, Hardisal (Sinkron : jurnal dan penelitian teknik informatika, 2020)
Draining traditional boat water efficiently is sometimes considered to be of little importance to most fishermen. Because it is considered a normal thing without realizing it can be detrimental, both in terms of time and work. One of the things that often makes the use of draining water less efficient is that the draining of boat water is still done manually with human intervention. So that fishermen are preoccupied with removing puddles of boats and hindering their work. Based on the above problems, this study aims to make a traditional boat water drain control system automatically. This tool functions to control the volume of water in the boat as well as turn on and turn off the water pump engine automatically. This tool is able to remove puddles that enter the fishing boat automatically. The working principle of this tool, if the water hits the sensor â‰¥ 5 cm, the pump and buzzer will start and if the water doesn't hit the sensor, the pump and buzzer will automatically shut down.